Effectiveness of Intralesional Steroid Injections in Peyronie’s Disease - Ali, Esha; Haider, Mohammad Zeeshan; Ullah, Irfan; Mubarik, Nazia; Mubarik, Nadia (Biological and Clinical Sciences Research Journal, 2025)
Peyronie’s disease (PD) is a progressive fibrotic disorder characterised by penile curvature, plaque formation, pain, and erectile dysfunction, significantly impacting patients’ quality of life. Various treatment modalities, including intralesional steroid injections, have been explored to manage PD, but their efficacy remains a subject of investigation. Objective: This observational study aimed to evaluate the effectiveness of intralesional steroid injections in treating Peyronie’s disease. Methods: This observational study was conducted from January 2023 to December 2024, involving 101 male patients aged between 20 and 65. All patients were diagnosed with Peyronie’s disease based on clinical evaluation and medical history. Participants were treated with intralesional steroid injections administered every four weeks for a total of three sessions. Pre- and post-treatment assessments included measurements of penile curvature, plaque size, erectile function using the International Index of Erectile Function (IIEF), and pain levels using a visual analogue scale (VAS). The primary outcomes were changes in penile curvature, erectile function, plaque size and pain relief, with follow-up evaluations conducted after each treatment cycle. Results: Out of the 101 patients, 75.2% experienced improvements in penile curvature, and 61.4% showed a reduction in plaque size. Additionally, 64.4% of participants reported pain relief, and 77.2% exhibited improvements in erectile function, as measured by the IIEF score. Conclusion: Intralesional steroid injections were found to be effective in reducing penile curvature, plaque size, and pain, as well as improving erectile function in patients with Peyronie’s disease.